Oxygen and ionic transport in hydrogel and silicone-hydrogel contact lens materials: An experimental and theoretical study - Pozuelo, Javier; Compañ, Vicente; González-Méijome, J.M.; González, María; Mollá, Sergio (Journal of membrane science, 2014)
The transport of oxygen, water and naked ions of Na+ and Cl− across two kind of hydrogels materials, made of a conventional hydrogel (Hy) based on hydroxyethyl methacrylate (pHEMA) and a silicone hydrogel (Si-Hy) material containing siloxane moieties, was compared between Molecular Dynamics Simulations (MDS) and experimental measurements. Computer-assisted simulations were carried out for wet hydrogels at 310K and equilibrium water uptake in the range from 10% to 40%. Our results show that in Si-Hy materials the aqueous hydrogel and hydrophobic siloxane phases are separated suggesting a co-continuous structure, and oxygen moves predominantly through the free volume of the hydrophobic siloxane phase. The values of diffusion coefficient of O2, water and Na+ and Cl− ions in Si-Hy was about one order of magnitude higher than in conventional hydrogels when the water content was above 25wt% up to a critical value of 35wt% where a percolation phenomenon is observed. The value of the oxygen diffusion coefficient obtained by simulations are roughly similar to that experimentally found using potentiostatic techniques. Values found experimentally for Na+ diffusion coefficients are between three or five times lower than MDS. For Si-Hy materials with 36wt% of water the Na+ permeability, diffusion coefficient and salt partition coefficient (km=P/D) are 6.7±0.2×10−7cm2/s, 1.8±0.5×10−6cm2/s and 0.42±0.13, respectively. For Hy materials of 38.6wt% the values found were 18.4±1.2×10−7cm2/s, 5.4±1.0×10−6cm2/s and 0.34±0.09, respectively. The coordination number between the fixed groups (SiO) and water in HEMA and the particles (O2, Cl− and Na+) is slightly larger than unity. The present study might be applied in the modeling of the gas transport in hydrogels as well as in novel polymeric structures for novel polymeric structures for new biomedical and technological applications with the aim of predicting and tuning their physiological behavior. Van der Waals surface showing the hydrophilic interface of a pHEMA-based with 37wt% water content (left) and a Silicone Hydrogel material with the same water content (right). [Display omitted] •MDS was used to study oxygen, water and ions transport in hydrogels.•Experimental values of oxygen diffusion and permeability have been determined.•The oxygen permeability in Si-Hy co-polymers is one order of magnitude higher than in hydrogels.•Diffusion coefficients of Na+ have been determined experimentally.•The Na+ diffusion coefficient is higher in conventional hydrogels than in Si-Hy.